Inflation Moderating Effect on Factors Affecting Stock Price Volatility - Widianegsih; Dede Djuniardi; Dendi Purnama (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2025)
This study aims to empirically test how the influence of asset growth, stock trading volume, dividend policy and leverage on stock price volatility with inflation as a moderating variable, in companies that are inconsistently settled in the LQ45 Index. The research sample includes 25 companies, comprising 125 observational data points collected over the period 2019–2023. Hypothesis testing was conducted using moderated regression analysis. The results indicate that the model is fit, with findings showing that asset growth, dividend policy, and leverage have a negative effect on stock price volatility. In contrast, trading volume has a positive effect on stock price volatility. Furthermore, inflation is proven to moderate the effects of all independent variables on stock price volatility. This study contributes to the literature on stock price volatility by offering a new approach through the incorporation of a moderating variable. Keywords: Stock Price Volatility; Asset Growth; Stock Trading Volume; Dividend Policy; Leverage